Facilitators and barriers to the implementation of selected local tuberculosis control programs in the Province of Laguna, Philippines - Antonio, Carl Abelardo T.; Guevarra, Jonathan P.; Medina, Paolo Victor N.; Roxas, Evalyn A.; Cavinta, Lolita L.; Manalo, Jorel A.; Ortega, Dorothy Jean N.; Cengca, Ma. Rhenea Anne M.; Lota, Rosario Clarissa Marie M.; Geocaniga-Gaviola, Donna Mae; Garfin, Anna Marie Celina G. (2021)
"This paper aimed to determine the facilitating and hindering factors in the implementation of local tuberculosis (TB) control programs in two purposively selected localities in the Province of Laguna, Philippines. Transcripts of semi-structured interviews with six policymakers and program implementers at the regional, provincial, and city/municipal levels were qualitatively analyzed in accordance with the method of Miles an co-athors and validated through triangulation and informant/stakeholder feedback" - title page.
Includes bibliographical references.
Keywords: Tuberculosis -- Philippines -- Laguna -- Prevention; Health services administration -- Philippines -- Laguna